(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Introduction: Lymphadenitis is the most common extrapulmonary manifestation of tuberculosis. It remains both diagnostic and therapeutic challenge as not only mimics other diseases but also inconsistent physical and laboratory findings. Diagnosis is difficult often requiring biopsy. Aim: Aim of the study was to evaluate the role of surgical dissection of tuberculous cervicle lymphadenopathy for diagnosis as well as therapeutic purpose. Methods: This observational study was conducted during the time period of 01 july 2015 to 30 june 2017 in ENT & Pulmonology department, combined military hospital Dhaka on 100 patients who have undergone surgical neck dissection. Result: In our study total 100 patients were biopsied. Among them 56 patient was diagnosed as tubercular lymphadenitis after lymphnode excision biopsy. Among them 47 tubercular lymphadenitis patient responded to ATT (CAT-1), only 2 patient developed cold abscess which required further surgery. Six patient showed relapse during follow-up and 9 patient did not respond to CAT-1 treatment (treatment failure). Surgical intervention along with CAT-2 treatment showed cure in all of them. 2nd surgical interventions were done in total 17 patients, 2 TB abscess during ATT (CAT-1 HRZE), 9 treatment failure patients and 6 relapse patients along with ATT (CAT-2 SHRZE) and all these patients had no relapse or treatment failure during further follow up. Bangladesh J Otorhinolaryngol; October 2017; 23(2): 127-132